FOSSIL REGISTER OF THE PALEONTOLOGICAL DIDACTIC MUSEUM OF OCUCAJE, ICA, PERÚ - Villaseca, Andrea (2020)
Th is study aims to create an offi cial register about fossil collections of the Didactic Paleontological Museum of Ocucaje. The paleontological collections present 45% of vertebrate fossils where there are cetacean vertebrae, two shark teeth, part of a seal skeleton, shark vertebrae, and an archaeocete skull. 20% is represented by fossil invertebrates such as a large number of internal molds of veneroids (clams), conglomerates of Turritela woodsi Lisson, 1925, gasteropods (Naticidae), and Mesodesmatidae (Macha). In total, 157 fossils have been coded and described, the fragments that represent 35% of the collection have not been included. Th e Pisco Formation has been considered as “fossil lagerstäten” for this reason it is strictly necessary the existence of a site museum that can house this paleontological diversity and maintain a constant curatorial activity.